Nutrition in tomato (Solanum lycopersicum L) as affected by light: Revealing a new role of phytochrome A - Carvalho, Rogério F. [UNESP]; Moda, Leandro R. [UNESP]; Silva, Gilmara P. [UNESP]; Gavassi, Marina A. [UNESP]; Prado, Renato M. [UNESP] (Southern Cross Publishing, 2016)
The far red light insensitive (fri) mutant of tomato, which is phytochrome A (phyA) deficient, displays some characteristics that have recently indicated important functions of this photoreceptor in water relations. With respect to the relationship between nutrition and water relations, we investigated the growth and nutritional status of fri supplied with Hoagland's complete solution and solutions with the individual omission of nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg) and sulfur (S). For this purpose, 20-day-old tomato plants of the WT (cv. Moneymaker) and fri mutant were transplanted into pots (one plant per pot) that contained Hoagland and Arnon (1950) solution diluted to 50 per cent in the first week and to 100 per cent from the second week of cultivation until the end of the experiment (50 DAT). Seven treatments were performed: a complete nutrient solution (KH2PO4, KNO3, Ca(NO3)2.5H2O, MgSO4.7H2O, KCl, CaCl2, H3BO3, MnCl2.4H2O, ZnCl2, CuCl2, H2MoO4H2O and Fe EDTA) and the individual omission N (KNO3, Ca(NO3)2.5H2O); P (KH2PO4); K (KH2PO4, KNO3); Ca (CaCl2); Mg and S (MgSO4.7H2O) from a balanced nutrient solution. The experiment was arranged in a completely randomized factorial design with two genotypes and seven types of nutrient solutions with three replications. Upon harvest, the following measurements were performed: the height of the plants, measured from the base of the stem of each plant to the insertion of the first fully expanded leaf; the stem diameter; the total number of leaves per plant; an indirect chlorophyll measurement, which we called the green color index, and the leaf area. Statistical analysis was performed using analysis of variance (ANOVA) followed by Tukey's test. First, based on growth analyses, fri showed an enhanced dry weight of the shoot, root and whole plant in complete solution compared with the wild type (WT). In addition, the phyA mutant had a multifaceted response compared with that of the WT when the nutrients were omitted. For the fri mutant, the height and green color index were reduced without N and K; the leaf area without P, K and S; the dry weight of the root and shoot without N, P, K and S, and the root, shoot and total plant dry weight without P, K and S. On the other hand, the green color index of the fri mutant was enhanced without Ca and Mg. Together, these results show that in addition to revealing an altered response to nutrition in the fri mutant, phyA can play a role in light signaling in the nutrition and nutritional stress of tomato.
Keywords: Abiotic stress; Mutant; Nutrition; Phytochrome; Tomato